Myocardial flow reserve derived from D-SPECT for evaluating non-culprit ischemic lesions in STEMI patients: comparison with quantitative flow ratio. - Zhao, Maomao; Xing, Erkun; Zhao, Jing; Chen, Fengmei; Chen, Ming; Lu, Andong; Pan, Chenliang; Bai, Lu; Zhang, Jing; Wa, Yongling; Wang, Ting; Zhao, Yanhang; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
Objectives: This study sought to elucidate the diagnostic performance and concordance between myocardial flow reserve (MFR) derived from dynamic single-photon emission computed tomography (D-SPECT) and quantitative flow ratio (QFR) in evaluating non-culprit ischemic lesions following ST-elevation myocardial infarction (STEMI). Additionally, the study investigated the integration of MFR with angiographic microvascular resistance (AMR) derived from coronary angiography to determine its utility in screening and stratifying non-culprit ischemic lesions. Background: The diagnostic performance and agreement between MFR and QFR in evaluating non-culprit ischemic lesions in STEMI patients with multivessel disease are unknown. Methods: This research encompassed a cohort of 106 STEMI patients with at least 1 intermediate non-culprit ischemic lesion, characterized by 40–80% diameter stenosis. After undergoing percutaneous coronary intervention, patients were evaluated using QFR and, approximately five days later, underwent D-SPECT to assess myocardial blood flow (MBF) and MFR. MFR was evaluated against QFR as a reference for diagnostic performance and agreement, including sensitivity analysis in vessels with normal microvascular function. Furthermore, MFR, combined with AMR, effectively screened and stratified non-culprit ischemic lesions. Non-culprit ischemic lesions were defined by QFR ≤ 0.80 and normal microvascular function by AMR < 255 mmHg*s/m. Results: Among non-culprit lesions, MFR predicted a QFR ≤ 0.80 with a sensitivity of 85%, specificity of 86%, and accuracy of 86%. The positive predictive value was 56%, and the negative predictive value was 96%. The MFR cut-off was 1.93, with an area under the receiver operating characteristic curve of 0.90 (95% CI: 0.84 to 0.94). MFR showed similar diagnostic performance in patients with normal microcirculation. Moreover, low MFR with normal AMR indicated non-culprit ischemic lesions caused solely by epicardial narrowing, while low MFR with abnormal AMR indicated ischemic lesions complicated by microvascular dysfunction. Conclusion: MFR derived from D-SPECT exhibits good diagnostic performance and moderate agreement in identifying non-culprit ischemic lesions in patients with STEMI. Combining AMR with MFR effectively screens and stratifies non-culprit ischemic lesions. Trial registration: ChiCTR.org.cn. ChiCTR2200059934. Registered 13 May 2022.